2019
DOI: 10.2485/jhtb.28.7
|View full text |Cite
|
Sign up to set email alerts
|

Second Order Differentiation Analysis of Micro FTIR Method Revealed the Variable Erosion Characteristics of Carbonated Soft Drink for the Individual Human Teeth Enamel

Abstract: To clarify the chemical processes of dental caries in detail, and to clarify whether or not the caries processes are common through the whole part of various teeth, the micro-FTIR spectroscopic analysis was carried out using the human teeth sections soaking into a carbonated soft drink (Sprite ® ) for 1 and 7 days. After the twenty human teeth examined, the teeth were grouped into two; the lightly dissolved one and extremely heavily dissolved one on the basis of the macroscopical and microscopical features aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…In this study, we could not prove the existence of β-TCP because we did not use Xray diffraction system, but we observed the changes caused by the substitution of the compound using a micro -FTIR instrument. which is thought to affect the crystal size (12) . According to the study of Holcomb et al (7) , pyrophosphoric acid is formed in parallel with the decomposition of HPO 4 2when heated above 500°C.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we could not prove the existence of β-TCP because we did not use Xray diffraction system, but we observed the changes caused by the substitution of the compound using a micro -FTIR instrument. which is thought to affect the crystal size (12) . According to the study of Holcomb et al (7) , pyrophosphoric acid is formed in parallel with the decomposition of HPO 4 2when heated above 500°C.…”
Section: Discussionmentioning
confidence: 99%
“…According to the peak values shown in Fig. 4; 3296, peaks in the band range of 2921 cm -1 (Ehrman et al, 1999;Jenkins et al, 2005a;Jenkins and Eagar, 2005b;Wang et al, 2006;Chen and He, 2008;Sowards et al, 2008;Sevilla and Fuertes, 2009;Gibot and Vidal, 2010;Saikia and Parthasarathy, 2010;Zheng et al, 2010;Vaculikova et al, 2011;Basu et al, 2011;Farzaneh and Najafi, 2011;Lin et al, 2012;Abdullah et al, 2014;Jamal et al, 2014;Golbabaei and Khadem, 2015;Naushad et al, 2015;Diko et al, 2016; Sahai et al, 2016;Benykhlef et al, 2016;Yi et al, 2018;Ge et al, 2019;Habtemariam et al, 2019;Bahah et al, 2019;Abinaya et al, 2019;Alias et al, 2019;Altunal et al, 2019;Boroń et al, 2019;Reddy et al, 2019;Karthik et al, 2019;Karunathilaka et al, 2019;Kono et al, 2019;Mohammadi et al, 2019;Ponmudi et al2019;Scaccia et al, 2019;Wang et al, 2019a;Wang et al, 2019b;Yang et al, 2019), indicate O-H bonding i...…”
Section: Characterization By Ftirmentioning
confidence: 99%
“…Welding fumes contain very different structures by its nature. 1139, 1257, 1407, 2848 and 2921 cm -1 peaks obtained from FTIR analysis were Al-O (Jamal et al, 2014;Benykhlef et al, 2016;Yi et al, 2018) (Abdullah et al, 2014;Golbabaei and Khadem, 2015), F 2 O 3 (Oberdörster et al, 2005), Mn-O (Jamal et al, 2014;Alias et al, 2019), N-O (Boroń et al, 2019;Yang et al, 2019), P-O (Kono et al, 2019), Pd-O (Reddy et al, 2019), Si-O (Saikia and Parthasarathy, 2010;Vaculikova et al, 2011;Diko et al, 2016;Bahah et al, 2019;Mohammadi et al, 2019) functional due to the fact that stretching of bonds of functional groups has increased.…”
Section: Characterization By Ftirmentioning
confidence: 99%
“…Artificial caries production was performed using the carbonated soft drink Sprite ® (Coca-Cola [Japan] Co. Ltd., Tokyo, Japan), and the durations of control, 1 day, and 7 days were fixed, as suggested by previous studies 1,2) . Twenty human third molar teeth used in this study were extracted for clinical reasons and pooled in purified water.…”
Section: Humantooth Samplesmentioning
confidence: 99%
“…From studies on human tooth enamel caries, it could be inferred that the appearances of native enamel caries and artificial carious lesions are determined by their diversities in original structural and physico-chemical properties 1,2) . Although the enamel crystallites revealed similarities to hydroxyapatite in electron diffraction and X-ray diffraction (XRD), our studies also revealed significant differences between the enamel mineral and pure hydroxyapatite [3][4][5][6] .…”
Section: Introductionmentioning
confidence: 99%